Trends in Public Policy in Labour Relations - Woods, H. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1965)
With the present paper, the author covers some of the developments which have known, since 1948, the various Canadian jurisdictions in the field of public policy and labour relations. The principal topics are: labour economics, labour-management relations and finally industrial peace and the changing role of government.